2015
DOI: 10.1302/0301-620x.97b5.35166
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of acetabular labral tears and associated pathology in a young asymptomatic population

Abstract: Acetabular labral tears and associated intra-articular pathology of the hip have been recognised as a source of symptoms. However, it is now appreciated that there is a relatively high prevalence of asymptomatic labral tears. In this study, 70 young asymptomatic adult volunteers with a mean age of 26 years (19 to 41) were recruited and underwent three tesla non-arthrographic MR scans. There were 47 women (67.1%) and 23 men (32.9%). Labral tears were found in 27 volunteers (38.6%); these were an isolated findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 37 publications
4
34
0
Order By: Relevance
“…There are numerous reports in the literature on the topic of asymptomatic labral tears, but with quite diverse findings. Lee et al performed MRI in 70 asymptomatic volunteers aged 19–41 years and found labral tears in 39% . Silvis et al reported 22 labral tears (56%) in 39 asymptomatic hockey players, a similar prevalence to that demonstrated in our study which evaluated asymptomatic participants from the general population.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…There are numerous reports in the literature on the topic of asymptomatic labral tears, but with quite diverse findings. Lee et al performed MRI in 70 asymptomatic volunteers aged 19–41 years and found labral tears in 39% . Silvis et al reported 22 labral tears (56%) in 39 asymptomatic hockey players, a similar prevalence to that demonstrated in our study which evaluated asymptomatic participants from the general population.…”
Section: Discussionsupporting
confidence: 87%
“…As labral and cartilage defects can also be encountered in healthy asymptomatic individuals, the association of these defects with symptoms of hip pain, and consequently their clinical relevance, is not entirely clear. The available data in the literature about the presence of labral tears in asymptomatic individuals are variable, with some studies reporting tears in 39%, 69%, or even 86% of volunteers . Few data are available on acetabular cartilage defects and almost no data is available on femoral cartilage defects in asymptomatic volunteers; moreover, in some studies, the authors did not distinguish whether a defect was located at the acetabulum or the femoral head …”
mentioning
confidence: 99%
“…In the hip, a common form of joint injury is an acetabular labral tear, which warrants further study as a possible contributing factor to the development of hip OA. Acetabular labral tears are very common, estimated to be present in 66% of people with mechanical hip pain [90] and roughly 39% of the asymptomatic population [91], with increasing age an important risk factor. The etiology of such tears can be an acute traumatic event, degenerative change of insidious onset such as is often caused by chronic impingement, idiopathic or occasionally congenital [92].…”
Section: Etiology and Risk Factors For Hip Oamentioning
confidence: 99%
“…As a significant proportion of the population has been reported to have asymptomatic cam lesions and labral tears, some question the utility of, and need for, surgery in the management of FAI [15, 18]. This debate has created a drive for a higher level of evidence to support the treatment of FAI.…”
Section: Discussionmentioning
confidence: 99%